2009
DOI: 10.1080/10683160802275797
|View full text |Cite
|
Sign up to set email alerts
|

A psychological perspective on vulnerability in the fear of crime

Abstract: This document is the author's final manuscript accepted version of the journal article, incorporating any revisions agreed during the peer review process. Some differences between this version and the published version may remain. You are advised to consult the publisher's version if you wish to cite from it. AbstractThis paper examines vulnerability and risk perception in the fear of crime. Past studies have often treated gender and age as proxies for vulnerability, and on the few occasions that vulnerabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
250
0
33

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(296 citation statements)
references
References 84 publications
(133 reference statements)
13
250
0
33
Order By: Relevance
“…Segundo, estos resultados permiten plantear que una línea de indagación muy interesante sería el análisis de la percepción del miedo al delito (Gainey, Alper y Chappell, 2010;Jackson, 2009). El gobierno ha desarrollado estrategias cuyo fin es reducir la inseguridad, tales como los botones de pánico en taxis y transporte público (conectados a la red policial para que apoyen rápidamente ante el robo), la colocación de cámaras en la ciudad y la creación del número de emergencia ecu-911.…”
Section: Discussionunclassified
“…Segundo, estos resultados permiten plantear que una línea de indagación muy interesante sería el análisis de la percepción del miedo al delito (Gainey, Alper y Chappell, 2010;Jackson, 2009). El gobierno ha desarrollado estrategias cuyo fin es reducir la inseguridad, tales como los botones de pánico en taxis y transporte público (conectados a la red policial para que apoyen rápidamente ante el robo), la colocación de cámaras en la ciudad y la creación del número de emergencia ecu-911.…”
Section: Discussionunclassified
“…For example, Box et al (1988) found that 50% of women in their sample expressed fear compared to 14% of men. Women also feel they are more at risk (e.g., Jackson, 2009) despite the fact that overall men are more likely to be victims of crime (e.g., Baumer, 1985;Lee, 2007). These gender differences may be subject to crime type.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived risk of vulnerability, also known as perceived likelihood of victimization (Ferraro, 1995), refers to the perceived likelihood or risk an individual has of becoming a victim or having a crime committed against them. In fact, considerably more people experience fear of crime rather than actual criminal victimization (Addington, 2011;Jackson, 2009). One explanation might be that fear includes a sense of vulnerability, both in terms of perceived likelihood of risk and perceived seriousness of the risk (Hale, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in their subjective perceptions with respect to the likelihood of being targeted by criminals, their ability to control a threatening situation and the consequences of becoming a victim of crime (see e.g. Skogan and Maxfield, 1981;Warr, 1984Warr, , 1985Warr, , 1987Killias, 1990;Ferraro, 1995;Smith and Torstensson, 1997;Jackson, 2009). To construct efficient policy tools that aim at reducing the overall adverse effects of crime on mental well-being it is crucial to understand the complexity behind the psychological mechanisms as to how fear of crime originates.…”
Section: Introductionmentioning
confidence: 99%